Italian healthcare professionals’ role in advancing reforms within the Italian National Healthcare System, as outlined in the National Recovery and Resilience Plan - Martina Giusti; Martina Giusti; Alessandro Beux; Alessandro Beux; Teresa Calandra; Stefano Lorusso; Paolo Amilcare Gazzaniga; Guglielmo Bonaccorsi; Giuseppe Greco; Niccolo Persiani; Niccolo Persiani (Frontiers in Public Health)
IntroductionIn 2021, the National Recovery and Resilience Plan (PNRR) outlined the foundational pillars for Italy’s economic recovery following the COVID-19 pandemic. Within PNRR’s Mission 6 “Health”, guidelines were established to reform the Italian healthcare system, focusing on community-based services and digitalization. This ambitious reform aims to shift from a hospital-centred model to a patient-centred one that promotes integrated provision of social and healthcare services.MethodsThe lack of institutional working groups to incorporate input from all Italian recognized healthcare professionals into PNRR’s implementation, the National Federation of Orders of Radiographers and Technical, Rehabilitative, and Prevention Health Professionals (FNO TSRM & PSTRP) addressed this gap by initiating a study.ResultsThe contributions from the 19 Italian Allied Health Professionals (AHPs) affiliated with the FNO TSRM & PSTRP were collected to identify priority areas and formulate actionable recommendations aimed at enhancing the organizational model of reformed Italian healthcare system outlined by the PNRR, which had been predominantly focused on nursing care.DiscussionAdopting a multi-professional and multidisciplinary approach could better address social and health needs of the population by leveraging the expertise of all registered Italian health professionals. This approach aligns Italian healthcare system with European standards, addressing issues such as task shifting and shortages in professional resources. Ultimately, this study provides concrete insights for Italian policymakers and healthcare leaders to foster greater inclusion of Italian AHPs in the design and implementation of the current and future reforms on national healthcare system.